(untitled) (Current Horticulture, 2024)
The experiment was conducted to analyze the status of root colonization by arbuscular mycorrhizal (AM) fungi and soil glomalin-related soil protein (GRSP) in plant of Osmanthus fragrans (YinGui) in the field. Three treatments, 1.0 m (S1.0m), 1.4 m (S1.4m) and 1.8 m (S1.8m) away from the trunk of plants of O. fragrans were designed. The results showed that plants were AM plants, as observed the AM structure. The AM colonization varied from 10.2% to 21.2% in field and greater mycorrhizal colonization was found in S1.4m. Easily extractable GRSP (EE GRSP) ranged from 0.457 to 0.565 mg/g soil and was higher in S1.4m than in S1.0m and S1.8m. No any significant difference was observed in difficultly extractable GRSP (DE-GRSP) and total GRSP. A greatly significantly positive correlation was found between AM colonization and EE-GRSP.